LGBTQ youth and education : policies and practices - Mayo, Cris. (New York : Teachers College Press, Columbia University, 2014)
"Based on the diverse experiences of LGBTQ students and their allies, this essential volume brings together in one resource the major issues that schools must address to improve the educational outcomes for gender and sexual minority students, as well as all students. Many of these issues involve negative school-based experiences that teachers and administrators need to be aware of as they interact with students on a daily basis, including those that encourage dropping out, substance abuse, and disproportionate thoughts of suicide. This insightful work not only examines the challenges of discrimination, harassment, and alienation that LGBTQ youth face, but it also captures students' resilience and creativity in organizing against those challenges. The text includes teaching strategies, innovative projects, curricular revisions, and policy initiatives that have had positive effects on LGBTQ learning, aspirations, and school climate. This book: offers a nuanced portrait of students, showing how issues of race, gender, gender identity, and class shape and complicate their experience; examines the history and contemporary movements for LGBTQ rights; describes a variety of discipline-based approaches to teaching students to think about LGBTQ-related concerns; shows examples of youth organizing into extracurricular groups or creating school- and community-based interventions, and highlights the role of online communities and web-based resources." -- Publisher's description.
Introduction -- Necessary tensions -- Layers of responsibility and professional sources for justification for nondiscrimination -- Students' rights to expression, privacy, and association -- Preparing teachers and leaders to be advocates -- 1. Background to LGBTQ movements for equality with a focus on K-12 related issues -- Key definitions, often in flux and contested -- Opening the subject of sexuality and gender through theory, history, and political movements -- Overlapping histories of LGBTQ movements -- Schools and the histories of gender identity and sexual orientation -- 2. Thinking through biases and assumptions about LGBTQ people -- Gender as process -- Sexuality, normalcy, and intersecting differences -- Transphobia in schools -- Queer relationalities -- 3. Specific school-related challenges facing LGBTQ students -- Intersecting harassments and biases -- LGBTQ youth and the challenges of accessing education -- Resituating "bullying" in sexual harassment -- Another form of "not" education: "you can't say gay" policies -- Recognizing family diversity: LGBTQ-headed households and school exclusion -- Living in families under public debate: legal and social contexts -- 4. Educatively addressing LGBTQ issues -- Zero tolerance and exacerbating distance -- Sex and non-sex -- Critical queer thinking and queer disciplines -- Religious tensions -- Teaching and learning for ethical relations -- 5. Supporting student extracurricular and creative efforts to educate schools on LGBTQ issues -- Gay-straight alliances and associations across difference -- Gay-straight alliances and the Equal Access Act -- Attempts to restrict gay-straight alliances -- The day of silence: resistance and reconciliation (hopefully) -- LGBTQ youth and public spaces -- 6. LGBTQ online communities and support -- LGBTQ digital divides -- LGBTQ youth, cyber presence, and intentional community -- Critical media literacy and cyber normalization -- The link made flesh -- Retooling and reassembling.
Includes bibliographical references (pages 117-131) and index.
Keywords: Homosexuality and education -- United States; Gay youth -- Education -- United States